2013
DOI: 10.2478/pjvs-2013-0059
|View full text |Cite
|
Sign up to set email alerts
|

The effect of PCB126, 77, and 153 on the intracellular mobilization of Ca+2 in bovine granulosa and luteal cells after FSH and LH surge in vitro

Abstract: Polychlorinated biphenyls (PCBs) are a group of persistent environmental pollutants that impair cattle reproduction. Among other effects, PCBs can disturb the intracellular mobilization of Ca +2 in several cell types. Hence, it is possible that they disrupt the transduction of intracellular signals generated from gonadotropin (FSH/LH) receptors. In steroidogenic ovarian cells, a defect in Ca +2 mobilization may have a detrimental influence on two important processes: the secretion of steroids (E2 or/and P4) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Polychlorinated biphenyls (PCBs) and pesticide DDT as well as its metabolite DDE are resistant to biodegradation (Borja et al 2005), and due to their lipophilic properties, they can accumulate in tissues of living organisms (Glynn et al 2000). These environmental pollutants can act as agonists or antagonists of gonadal steroid hormones (Goldman and Yawetz 1992, Safe 1994, Schrader et al 2003, influence oxytocin (OT) secretion (Mlynarczuk et al 2009, Wrobel et al 2014, and decrease the sensitivity of granulosa and luteal cells to gonadotropins (Mlynarczuk and Kowalik 2013). We observed that these xenobiotics (XBs) in concentrations detected in the reproductive tract (Kamarianos et al 2003, Mlynarczuk et al 2005) disturb the secretory function of the ovaries and both contractions and secretory functions of the uterus and oviducts during the estrus cycle and pregnancy (Mlynarczuk et al 2009, Wrobel et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Polychlorinated biphenyls (PCBs) and pesticide DDT as well as its metabolite DDE are resistant to biodegradation (Borja et al 2005), and due to their lipophilic properties, they can accumulate in tissues of living organisms (Glynn et al 2000). These environmental pollutants can act as agonists or antagonists of gonadal steroid hormones (Goldman and Yawetz 1992, Safe 1994, Schrader et al 2003, influence oxytocin (OT) secretion (Mlynarczuk et al 2009, Wrobel et al 2014, and decrease the sensitivity of granulosa and luteal cells to gonadotropins (Mlynarczuk and Kowalik 2013). We observed that these xenobiotics (XBs) in concentrations detected in the reproductive tract (Kamarianos et al 2003, Mlynarczuk et al 2005) disturb the secretory function of the ovaries and both contractions and secretory functions of the uterus and oviducts during the estrus cycle and pregnancy (Mlynarczuk et al 2009, Wrobel et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the present study aimed to determine whether GLY directly affects ovarian function. To address this aim, bovine granulosa cells (GC) and theca cells (TC), which represent an intriguing in vitro model to study contaminant reproductive effects (Mlynarczuk & Kowalik, ; Mlynarczuk et al ., ; Petro et al ., ; Pizzo et al ., ,b; Spicer & Aad, ) were used and the effects of GLY on ovarian cell proliferation, steroid production and gene expression were evaluated.…”
Section: Introductionmentioning
confidence: 99%